Aerobics Trainers' Use of Real-Time Feedback Technology and Clients' Performance Improvements in Aerobic Fitness Tests in Inner Mongolia, China - Guan, Bei (Pacific International Journal, 2025)
This study investigates the relationship between aerobics trainers' use of real-time feedback technology (RTFT) and client performance improvements in aerobic fitness tests. Conducted at Baotou Light Industry Vocational Technical College in Inner Mongolia, China, the research employed a descriptive-comparative-correlational design. Eighty-four aerobics trainers were surveyed on their demographic profiles, self-assessed use of RTFT (including frequency of use, technical skill, data interpretation, and real-time adjustments), and their assessment of client improvements (in cardiovascular endurance, recovery time, test scores, and performance consistency). Results indicated a significant positive correlation between trainers' self-assessed proficiency with RTFT and their reported client performance gains. While trainers were generally confident, areas for improvement were identified in consistent technology application and advanced data interpretation. The findings underscore the value of RTFT in enhancing training efficacy and highlight the need for targeted professional development to maximize its potential.